On the correct estimation of the magnetic entropy change across the magneto-structural transition from the Maxwell relation: Study of MnCoGeBX alloy ribbons - (:unkn) unknown (ELSEVIER SCIENCE SA, 2017)
An accurate calculation of the different magnetocaloric-related magnitudes derived from the temperature dependence of the magnetic entropy change in materials exhibiting first-order magnetocaloric effect is imperative to correctly estimate the true potential of a specific material for refrigeration purposes. In this contribution, we present a meticulous study of two different thermal procedures to measure the set of isothermal magnetization curves from which the total field induced magnetic entropy change, Delta S-T, is calculated using the adequate Maxwell relation. If the accurate determination of Delta S-T for any temperature is pursued the thermal and magnetic history of the materials must be taken into account, and then, the unidirectional measurement of reversible isothermal magnetization curves after a thermal cycle is required. The analysis was conducted on MnCoGeB0.01 alloy ribbons that show a giant Delta S-T at the coupled magneto-structural transition, from a ferromagnetic (TiNiSi-type) phase to a paramagnetic (NiIn2-type) one, owing to the concomitant abrupt magnetization change. We suggest that the conclusions reached can be applicable to any other system displaying magnetocaloric effect originated at a first order phase transition. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: First order magnetocaloric effect; Maxwell relation applicability; Magnetic entropy change; Refrigerant capacity; MnCoGeBx alloys; MARTENSITIC-TRANSFORMATION; MAGNETOCALORIC PROPERTIES; SIZE